Corrosion behavior and mechanism of Cr10Mo1 steel subjected to different corrosive ions in simulated concrete pore solution - Junxiang Yuan; Guojian Liu; Lin Yang; Yunsheng Zhang (Journal of Materials Research and Technology)
The corrosion of pre-passivated Cr10Mo1 steels in simulated concrete pore solution of saturated Ca(OH)2 induced by different corrosive ions were investigated, namely Cl−, SO2- 4, and combination of Cl− and SO2- 4. Electrochemical methods, Pourbaix analysis of Fe–Cr–H2O system and DFT calculation were adopted to characterize corrosion behavior and reveal underlying mechanism. Results showed that while sulfate may induce corrosion at higher threshold value, the scenario of chloride alone leads to lowest corrosion potential, linear polarization resistance and highest corrosion rate, and the presence of SO2- 4 ions mitigate corrosion risk under the coexistence condition of chloride and sulfate. A two-step reaction model of competitive adsorption-catalytic corrosion was proposed based on theoretical analysis and DFT calculation results.